Cervical curvature variations in patients with infraocclusion. (21st May 2014) - Ando, E.; Shigeta, Y.; Hirabayashi, R.; Ikawa, T.; Hirai, S.; Katsumura, S.; Ogawa, T.
Summary The purpose of this study was to observe the variations of cervical curvature in patients with infraocclusion, and to compare this with the controls. In this study, the infraocclusion criteria were defined with the Pr‐id as <17 mm on the cephalometric image. The subjects were 32 patients with infraocclusion, and 28 controls which matched the distribution for gender and age. The six points of inquiry were as follows: (i) cervical vertebra height, (ii) neck alignment, (iii) ratio of lower facial height, (iv) vertical dimension of occlusion, (v) cervical angle and (vi) occlusal angle. In over 90% of the patients with infraocclusion, the cervical curvature was classified as straight or kyphosis. Conversely, in 36% of the control subjects, the cervical curvature was classified as Lordosis. There was a weak positive correlation between the vertical dimension of occlusion and the cervical curvature in all subjects. In the control group, there was a significant and strong positive correlation between the age and cervical curvature, and a strong negative correlation between age and cervical angle and occlusal angle. Conversely, in the patients with infraocclusion, age was only correlated with the ratio of lower facial height. The prevalence of non‐lordosis in the patients with infraocclusion was higher in comparison with the control group in our study, and the previous large‐scale study of Japanese. However, there was merely a weak positive correlation between the cervical curvature and the vertical dimension of occlusion.